Pengaruh Air Perasan Daun Pepaya terhadap Kematian Larva Aedes albopictus dalam Upaya Pencegahan Penyakit Demam Berdarah Dengue - Nita Rahayu; Harninda Kusumaningtyas; Eni Purwaningsih; Ritna Udiyani; Bayu Purnama Atmaja; Mahruddin Hatim Habe (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2022)
Dengue Hemorrhagic Fever (DHF) is one of the vector-borne diseases which is still a public health problem in Indonesia. Efforts are needed to control mosquitoes both in the larval and adult stages. Papaya leaf could be a natural larvicide that is more environmentally friendly in an effort to control dengue vector. The purpose of the study was to determine the effect of giving papaya leaf juice to the mortality of Aedes albopictus larvae. This research is quasi-experimental research design with post test only with control group design, with a sample of 30 third instar larvae divided into two groups, papaya leaf juice and aquadest. post test was carried out 4 times at 6, 12, 18 and 24 hours. The results of the study in the intervention group (50 ml of papaya leaf juice plus 200 ml of plain water in a paper cup/container) and the control group using 200 ml (aquadest) after the first 6 hours of treatment there were no deaths (0%), the 12th hour a small percentage of 5 deaths larvae (16.6%), at the 18th hour almost half of 12 larvae died (40%) and at the 24th hour most of the 18 (60%) Aedes albopictus larvae died. While the control group observed 6, 12, 18, 24 hours overall (100%) live Aedes albopictus larvae. There is an effect of giving papaya leaf juice to the mortality of Aedes albopictus larvae after 24 hours of observation. Leaf juice may be used as a larvicide in an effort to prevent the incidence of Dengue Hemorrhagic Fever.